2003
DOI: 10.1084/jem.20030169
|View full text |Cite
|
Sign up to set email alerts
|

Cooperating Mechanisms of CXCR5 and CCR7 in Development and Organization of Secondary Lymphoid Organs

Abstract: Homeostatic chemokines participate in the development of secondary lymphoid organs and later on in the functional organization of these tissues. The development of lymph nodes (LNs) and Peyer's patches depends on the recruitment of CD3− CD4+ interleukin (IL)-7Rαhi cells to sites of future organ development. CD3− CD4+ IL-7Rαhi cells express the chemokine receptor CXCR5 and might be attracted by its ligand CXCL13, which is secreted by mesenchymal cells. Mesenchymal cells also secrete CCL19, a ligand for CCR7, ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
149
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 172 publications
(159 citation statements)
references
References 17 publications
8
149
0
Order By: Relevance
“…23 Intestinal tissue from RANKL Ϫ/Ϫ mice and controls was stained with antibodies to CXCL13. In control mice, Figure 3.…”
Section: Cxcl13 Is Not Expressed Within Cps In the Small Intestine Ofmentioning
confidence: 99%
“…23 Intestinal tissue from RANKL Ϫ/Ϫ mice and controls was stained with antibodies to CXCL13. In control mice, Figure 3.…”
Section: Cxcl13 Is Not Expressed Within Cps In the Small Intestine Ofmentioning
confidence: 99%
“…CCL21 and CXCL13 are ligands for CCR7 and CXCR5 (expressed by B cells), respectively, and are secreted by mesenchymal cells in the early developing lymph node to drive lymphoid tissue formation through the attraction of CD3ε − CD4 + IL-7Rα hi CCR7 + and CXCR5 + lymphoid tissue inducer cells [62,66]. The 3D organization of the lymph node is also driven and maintained by these cytokines; FRCs of the T cell zone express CCL21 and CCL19, which guide the interactions between CCR7 + T cells and APCs, while follicular dendritic cells express CXCL13 to define and maintain zones of CXCR5 + B cells [67].…”
Section: Secondary Lymphoid Organsmentioning
confidence: 99%
“…Although the cooperative function and reciprocal distribution of CXCR5 and CCR7 ligands in secondary lymphoid organ embryogenesis and post-natal life have been documented [1,9], no data are currently available about the mutual distribution of CCL21-and CXCL13-producing cells under inflammatory conditions and in the developing synovial lymphoid tissue. To address this point, we performed immunohistochemistry (IHC) and in situ hybridization (ISH) for CCL21 on sections sequential to those stained for CXCL13.…”
Section: Ccl21 In Situ Production and Microstructural Lymphoid Organimentioning
confidence: 99%
“…They have been implicated in lymphocyte recruitment from the bloodstream [2][3][4], the structural compartmentalization of T-B microdomains [5][6][7] and T-B cell interactions within the tissue [8]. Recent studies have demonstrated that the same chemokines (CK) are required for the embryonic development and organization of the majority of secondary lymphoid organs [9], being produced by a subset of mesenchymal cells (VCAM-1 + LTbR + , "organizers") in the early lymphoid anlagen [10,11]. It has been suggested that these CK contribute to the clustering of the earliest wave of hematopoietic cells (CD3 -CD4 + LTb + , "inducers"), preceding peripheral node addressin (PNAd) + high endothelial venule (HEV) formation, T-B lymphocyte compartmentalization and follicular dendritic cell (FDC) network development [12].…”
Section: Introductionmentioning
confidence: 99%